Amphibian skin bacteria display antifungal activity and induce plant defense mechanisms against Botrytis cinerea - Romero-Contreras, Yordan J.; Gonzalez-Serrano, Francisco; Formey, Damien; Aragón, Wendy; Chacón, Florencia Isabel; Torres, Martha; Cevallos, Miguel Ángel; Dib, Julian Rafael; Rebollar, Eria A.; Serrano, Mario (Frontiers in Plant Science, 2024)
Botrytis cinerea is the causal agent of gray mold, which affects a wide variety of plant species. Chemical agents have been used to prevent the disease caused by this pathogenic fungus. However, their toxicity and reduced efficacy have encouraged the development of new biological control alternatives. Recent studies have shown that bacteria isolated from amphibian skin display antifungal activity against plant pathogens. However, the mechanisms by which these bacteria act to reduce the effects of B. cinerea are still unclear. From a diverse collection of amphibian skin bacteria, three proved effective in inhibiting the development of B. cinerea under in vitro conditions. Additionally, the individual application of each bacterium on the model plant Arabidopsis thaliana, Solanum lycopersicum and post-harvest blueberries significantly reduced the disease caused by B. cinerea. To understand the effect of bacteria on the host plant, we analyzed the transcriptomic profile of A. thaliana in the presence of the bacterium C32I and the fungus B. cinerea, revealing transcriptional regulation of defenserelated hormonal pathways. Our study shows that bacteria from the amphibian skin can counteract the activity of B. cinerea by regulating the plant transcriptional responses.